UTAUT: Integrating Achievement Goals and Learning Styles for Undergraduates' Behavioural Intention to Use Technology - T.C.Y. Tey; P. Moses (European Alliance for Innovation (EAI), 2018)
In Malaysia, technology use is much emphasised as the Ministry of Education foresees great potential of technology use in amplifying students' learning. However, the great potential of technology use has not been fully realised. Therefore, the purpose of this study was to explore the influence of the existing antecedents in the Unified Theory of Acceptance and Use of Technology (UTAUT) model with two additional variables (achievement goal and learning styles) on undergraduates' behavioural intention to use technology. This study also aimed to determine the best predictor of undergraduates' intention to use technology. Hence, a quantitative survey method involving 699 undergraduates was employed in this study. The findings indicated that the undergraduates' effort expectancy, performance expectancy, social influence and achievement goals had significant influence on their behavioural intention to use technology. This study provides insights to the education stakeholders on the necessity to enhance pedagogical technology innovations in the higher education system.